The side effects of mass tourism: the voices of Bali islanders - Chong, Daniel Ka Leong * (Taylors & Francis, 2019)
This research extends preceding academic efforts concerning the impacts of mass tourism to the socio-cultural well-being of the hosts. A total of 20 Bali islanders who have met the predetermined criteria were sampled. Results suggesting that mass tourism development not only influences the local environment, economy, and business governance but more importantly the people, culture, heritage, and traditions. Even though that mass tourism in Bali remains to offer financial opportunities and stimulating infrastructural growth, nevertheless, the opportunity costs that the tourism development of Bali has to bear is the trade-off of environmental, cultural, and social meaning to the local community.